2019
DOI: 10.1073/pnas.1819965116
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic super-resolution structured illumination imaging in the living brain

Abstract: Cells in the brain act as components of extended networks. Therefore, to understand neurobiological processes in a physiological context, it is essential to study them in vivo. Super-resolution microscopy has spatial resolution beyond the diffraction limit, thus promising to provide structural and functional insights that are not accessible with conventional microscopy. However, to apply it to in vivo brain imaging, we must address the challenges of 3D imaging in an optically heterogeneous tissue that is const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 30 publications
(36 reference statements)
2
103
0
Order By: Relevance
“…In super-resolution imaging (∼50 nm resolution), cells, cell processes or tracked molecules that move faster than 50 nm per acquisition frame will not be imaged accurately. Thus, faster super-resolution imaging techniques, such as SIM (at least 9.3 Hz) (Turcotte et al, 2019) Fig. 3.…”
Section: Super-resolution Microscopymentioning
confidence: 99%
“…In super-resolution imaging (∼50 nm resolution), cells, cell processes or tracked molecules that move faster than 50 nm per acquisition frame will not be imaged accurately. Thus, faster super-resolution imaging techniques, such as SIM (at least 9.3 Hz) (Turcotte et al, 2019) Fig. 3.…”
Section: Super-resolution Microscopymentioning
confidence: 99%
“…Its fast response allows the deformable mirror (DM) to be adjusted for every image frame when imaging dynamic processes in live samples. Turcotte et al [34] reported a combination of 2D SR-SIM (increased lateral resolution and optical sectioning) and direct wavefront sensing AO to image the dynamics of dendrites and dendritic spines in the living mouse brain in vivo. However, the direct wavefront sensing method requires a dedicated wavefront sensing system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using these displacements, the SHS can reconstruct the wavefront, determine its constituent Zernike modes and thus the corrective phase that needs to be added to the system. This approach to aberration correction has been used to recover the optimal resolution of 2PE laser scanning [27,28] and structured illumination [29,30] microscopes deep in tissue, including in a living mouse [30,31].…”
Section: Introductionmentioning
confidence: 99%